LINGUISTIC REPRESENTATION OF PROFESSIONAL IDENTITY IN STUDENT-WRITTEN BIOGRAPHIES OF MICE INDUSTRY FIGURE - Narolita, Mella (Jurnal Education and Development, 2025)
This study explores how professional identity is constructed linguistically in biographies written by MICE (Meeting, Incentive, Convention and Exhibition) students within an English for Specific Purposes (ESP) context. Using a descriptive qualitative design, the study analyzed twenty-five biographies of MICE industry figures written by first-year students. A thematic linguistic analysis identified recurring words, phrases, and evaluative expressions used to represent professional identity. Novelty lies in using student-authored biographical writing to connect ESP genre learning with professional identity construction in a vocational MICE setting. The findings show that students predominantly use evaluative and action-oriented language, with professionalism and leadership emerging as the most salient themes. Additional themes include collaboration, hospitality orientation, innovation, and achievement. These identities are mainly realized through positive adjectives, action verbs, and role-based noun phrases, resulting in idealized portrayals of MICE professionals. The study highlights the pedagogical value of biographical writing as a genre that supports language development and professional socialization in vocational ESP settings. It contributes to discussions of professional literacy by showing how students interpret and express industry values through language, offering insights for improving ESP instruction in MICE education.